G550(P) What matters to families of children with complex medical needs? Co-designing an information leaflet for children with complex medical needs. (25th October 2020) - Gough, J; Roberts, S; Gray, T; Sheeley, R; Neilson, S; Pawlak, L; Wicks, C; Ramachandran, R
Abstract : Aim: To improve communication between healthcare professionals and families/carers of children with complex medical needs, we co-designeda patient information booklet, to be given on admission to our ward. Methods: A focus group involving six families of children with medically complex needs was held with the aid of our Patient Engagement lead. Four questions were asked: In hindsight, what information do you wish you had known or been given on admission to hospital or following diagnosis? What information could we give you that would make your lives easier? What advice would you give other parents in a similar situation? What other resources or contacts have helped you? The resulting information informed the creation of a patient information booklet. Results: The work highlighted the importance of seeking patient input, whilst our anticipation had been a focus on medical information, their desire was for much more practical information related to their wider context. Reflecting their longer stay; knowledge of accommodation, food choices and parking were key with one family highlighting they had spent £1000 on parking. In keeping with literature reporting on the high psychosocial and financial burden on these families, information on how to get financial support and signposting to charities that aided with this were valued. Interestingly families had mixed feelings about parent run support groups. Results also made us question common ward practices with parents talking of the emotional distress caused by repeatedly recounting their child's, often difficult, medical journey. Many found being part of multidisciplinary meetings overwhelming and wanted greater choice over how they were involved. They wanted the important role of allied health professionals to be clearer from the start. Stories also illustrated how misleading commonly used medical phrases such as 'Delayed development' can be. Amongst the advice they would give to families they commented on the importance of not losing hope and trusting your own parental instinct; as a result families' own stories and words of advice have been included in the information leaflet. Conclusion: The involvement of families is vital in co-designing any information given to families of children with complex medical needs.